Uma extensão do método OOWS para linha de produto de software - Souza, Bruno Miguel Nogueira de (2008)
Web applications are software products that work in the Internet. The development of Web applications has significantly increased in the last years due to its portability and visibility. Thus, several companies are migrating their applications to information systems accessible through the Internet. However, the quality of these applications has not been increasing proportionally. Most of the Web application development methods aim at producing complete applications, without considering software reuse. One of the most successful techniques of reuse is Software Product Line (SPL). A SPL contains a core asset that characterizes a family of applications of a certain domain. Amongst the Web application development methods, we chose to investigate and adapt the OOWS (Object Oriented Web Solution) due to its compatibility with SPL techniques. Thus, this dissertation presents an extension to OOWS, named SPL-OOWS, to improve the development of Web application with reuse. A basic framework was developed from which Web applications can be generated. This framework contains: Form Management, User Management and Persistence Management. The specification stages were redefined to include variability definition and tracing. A configuration stage was included to manage the artifacts obtained in the specification stage to create the presentation and navigation models. SPL-OOWS was evaluated through the development of an application example in which important issues were explored. Evidences show that there is an adoption cost, but once a domain becomes mature, the development cost is reduced and the productivity increases as there is no need to create new models but just to configure the existent ones in order to satisfy the requirements of an application of the same domain.